Effect of kinesio taping intervention on the muscle strength and balance of college basketball players with functional ankle instability - Li, Rui; Qin, Rui; Tan, Yajun; Liu, Hengxian; Wang, Kun; Cheng, Liang (Frontiers in Physiology, 2023)
Objective: The aim of this study was to investigate the effects of acute Kinesio Taping (KT) intervention on the muscle strength and balance ability of college basketball players with functional ankle instability (FAI). Methods: Thirty college basketball players with FAI were treated with acute KT to test the changes in their muscle strength and balance ability. Results: After acute KT intervention, the ankle dorsiflexion moment and the ankle plantar flexion moment increased by 34% and 19.9%, respectively. The stable plane test with the subjects’ eyes open decreased by 1%, whereas that with the subjects’ eyes closed decreased by 1.1%. The swaying environment test with the subjects’ eyes open increased by 2.4%. The swaying plane test with the subjects’ eyes open increased by 5.1%, whereas that with the subjects’ eyes closed increased by 16.2%. The swaying environment test with the subjects’ eyes open plus the use of a plane increased by 12.1%. Conclusion: KT can increase the isokinetic strength of the ankle dorsum muscle and plantar flexion of college basketball players with FAI. The effect of KT in the static balance test was weaker than that in the dynamic balance test. The findings indicate that KT can significantly improve the balance ability of college basketball players with FAI during dynamic sports.